Buber e Weber em torno da política e da ética: o vértice da decisão valorativa como espaço para a dialogia - GOUVÊA, Mário de Oliveira (Universidade Federal do Pará, 2012)
Weber, as we will perceive later, assumed as challenge the attempt to point a rescue with respect to the possible corrosion of the politics in modernity, therefore at a historical time marked by the enterprise perception, a difficulty consists to make with that the politics assumes the vocation characteristic. Buber will assume the importance for the understanding of a bias it to act deriving of one another interpretative source of the politics, distinct of the classic traces of modernity occidental person, contributing decisively for the elaboration of the firmed ethical decision in a valor religious in the Jewish mistic and the Hebrew humanism. Which would be then the conditions it politics to assume a worthy relation with the ethics, in an age marked for the depreciation of all the values? Or in an enlightenment of conception, as to donate to the politics the possibility to inside retake the principle of the emancipation of the proper effectiveness, incorporating the necessity of “answering ethical” in relation to the face of the other? Questions as the pointed ones above are the foundations that had motivated this research.